2022
DOI: 10.3390/microorganisms10112163
|View full text |Cite
|
Sign up to set email alerts
|

Linking Puberty and the Gut Microbiome to the Pathogenesis of Neurodegenerative Disorders

Abstract: Puberty is a critical period of development marked by the maturation of the central nervous system, immune system, and hypothalamic–pituitary–adrenal axis. Due to the maturation of these fundamental systems, this is a period of development that is particularly sensitive to stressors, increasing susceptibility to neurodevelopmental and neurodegenerative disorders later in life. The gut microbiome plays a critical role in the regulation of stress and immune responses, and gut dysbiosis has been implicated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 229 publications
0
4
0
Order By: Relevance
“…Animal and human studies have demonstrated a clear correlation between altered microbial composition and altered behavior [164][165][166][167][168][169][170][171][172], mental disorders [173][174][175], and the development of neuroinflammation [158,[176][177][178][179][180][181]. The intestinal microbiota communicate with the brain via the neural, immune, and metabolic pathways and impact neuronal plasticity and cognition [66,182,183]. This communication takes place either directly via the vagus nerve or indirectly via microbial-derived metabolites, as well as intestinal-derived metabolites, intestinal-derived hormones, and endocrine peptides [3,184].…”
Section: Dysbiosis Behavior Mental Disorders and Neuroinflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal and human studies have demonstrated a clear correlation between altered microbial composition and altered behavior [164][165][166][167][168][169][170][171][172], mental disorders [173][174][175], and the development of neuroinflammation [158,[176][177][178][179][180][181]. The intestinal microbiota communicate with the brain via the neural, immune, and metabolic pathways and impact neuronal plasticity and cognition [66,182,183]. This communication takes place either directly via the vagus nerve or indirectly via microbial-derived metabolites, as well as intestinal-derived metabolites, intestinal-derived hormones, and endocrine peptides [3,184].…”
Section: Dysbiosis Behavior Mental Disorders and Neuroinflammationmentioning
confidence: 99%
“…Overall, research suggests that dysbiosis of the intestinal microbiota and increased intestinal permeability (commonly, but not exclusively, due to dysbiosis) can affect brain function, mental health, and behavior [3,16,31,35,[57][58][59][60][61][62][63][64][65][66].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of LPS treatment on increasing inflammatory cytokine levels shortly after exposure in the serum and tissues has been reported [6,57]. A difference in the acute immune responses to LPS exposure has been found between puberty and adulthood, indicating that immune responses to immune stressors are highly affected by age [58]. We found that prebiotic administration diminished the immediate effects of pubertal LPS exposure on IL-17A and F, TGF-β, IL-6, IL-1β, and IL-23.…”
Section: Discussionmentioning
confidence: 99%
“…The microbiome has the ability to influence host stress responses by interacting with the neuroendocrine system and the hypothalamic-pituitary-adrenal (HPA) axis [160,161]. Commensal microorganisms can impact the production and signaling of stress hormones, which ultimately affect immune function and susceptibility to infections [162].…”
Section: Microbiome-induced Changes In Host Barrier Permeabilitymentioning
confidence: 99%